A Moral Appraisal of Euthanasia Beliefs and Practices in Urhoboland - Ikolo, Michael; Ottuh, Peter (dialektika kontemporer, 2024)
This article examines the moral dilemma of likely euthanasia practices in Urhoboland and uses the moral frameworks of prudential personalism, Ubuntuism, and the principles of nonmaleficence, beneficence, and autonomy to appraise the practices. The study employs historical and phenomenological approaches. It collected relevant data from community leaders, elders, and medical experts from five selected Urhobo kingdoms. The finding shows that euthanasia in all its forms is a practice that dehumanizes and destroys human dignity and does not promote African culture and humanism, even though some African communities still engage in euthanasia-like practices unknowingly. It also reveals that these behaviours are now declining considerably in most Urhobo and other African communities due to modernity, advanced healthcare systems, and sound religious teachings. It concludes that community and religious leaders should discourage fetish beliefs and traditions and promote the humanity of the vulnerable individuals in their communities.